Genetic counselling: a psychological conversation - Clarke, Angus (Professional Ethics, 2006)
Contributions to this study are drawn both from health professionals engaged in genetic counselling and from observers and critics with backgrounds in law, philosophy, biology, and the social sciences. This diversity will enable health professonals to examine their activities with a fresh eye, and will help the observer-critic to understand the ethical problems that arise in genetic counselling practice, rather than in imaginary encounters.Most examinations of the ethical issues raised by genetics are concerned in a broad sense with the application of new technology to human reproduction. This volume focuses on genetic counselling and screening as such, providing valuable insights for the health professional, social scientist, philosopher, lawyer, and bioethicist.